Faktor – Faktor Yang Mempengaruhi Kejadian Baby Blues Syndrome Pada Ibu Nifas di PMB Linda Elisabet Kota Depok Jawa Barat - Barus, Maghdalena; Oktaviani Zai, Kristina (Miracle Journal, 2024)
The first week following giving birth is a common time for the mild affective disorder condition known as Baby Blues or Maternity Blues. The third to fifth day after delivery is when the occurrence of Baby Blues Syndrome rises, and it continues for fourteen days thereafter. This study falls under the category of analytical observational research since it does not treat research subjects in any way to help researchers understand the issue more thoroughly. This study used a cross-sectional design and was a survey in nature. Forty women who gave birth at PMB Linda Elisabet Elisabet in May 2024 and were at least one week postpartum made up the study's group. The researchers in this study used the total sampling formula to choose their samples. Sequential sampling was employed for the sampling process. The study found no statistically significant correlation (p = 0.477) between postpartum mothers' age and the frequency of infant blues syndrome in PMB Linda Elisabet, Depok City, West Java in 2024. Parity is statistically associated with a lower risk of postpartum blues syndrome in PMB moms. Depok City, West Java's Linda Elisabet in 2024, p = 0.024, Baby blues syndrome incidence and pregnancy status are statistically related in 2024 at PMB Linda Elisabet in Depok City, West Java. The p-value for this relationship is 0.041, suggesting that the two variables are significantly related. The goal of PMB Linda Elisabet's baby blues syndrome screening program is to reduce the prevalence of postpartum depression and encourage moms to talk to their loved ones about the challenges they're experiencing.